Taxation policy in EMU - Alworth, Julian; Arachi, Giampaolo; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
This paper proposes to examine whether and how the introduction of the euro changed the impact of taxes on the economy or influenced the direction of tax policy. The paper surveys potential theoretical channels through which tax policy and exchange rate regimes are interrelated (capital mobility, strategic tax setting and trade policy). It is difficult to find strong empirical evidence of major, unique changes in the impact or determination of tax policy following the introduction of the euro owing. The internal market has had by far a greater impact and it has affected all European Union countries. Nevertheless, we highlight that going forward certain specific aspects deserve attention. The most important concerns the use of tax policy by individual EMU countries to improve competitiveness by changing the mix of taxes and thereby achieving an internal devaluation. A second issue deserving attention concerns tax competition particularly in the area of corporation tax. We provide some tentative evidence that capital movements to and from euro area countries have become more responsive to the levels of corporate taxation.
Economic Papers